Kinetic of CO2 absorption and carbamate formation in aqueous solutions of diethanolamine - Benamor, A.; Ali, B.S.; Aroua, M.K. (Korean Journal of Chemical Engineering, 2008)
The absorption rates of CO2 into aqueous solutions of Diethanolamine (DEA) with varying concentrations from 0.2 to 4M and temperature range from 293 to 323 K were measured by using a laboratory stirred reactor. The CO2 partial pressure was varied in a range that the reaction would occur in pseudo first order regime. Experimental data were analyzed and the kinetic parameters associated with the reaction were determined. The activation energy for the deprotonation of the intermediate zwitterion was estimated at about 11.4 kcal/mol. The contribution of carbamate formation to the overall absorbed CO2 was experimentally evaluated and found to be of the order of 100.